Quantification of Heterogeneous Degradation in Li‐Ion Batteries. Issue 25 (28th May 2019) - Yang, Yang; Xu, Rong; Zhang, Kai; Lee, Sang‐Jun; Mu, Linqin; Liu, Pengfei; Waters, Crystal K.; Spence, Stephanie; Xu, Zhengrui; Wei, Chenxi; Kautz, David J.; Yuan, Qingxi; et al.
Abstract: The multiscale chemomechanical interplay in lithium‐ion batteries builds up mechanical stress, provokes morphological breakdown, and leads to state of charge heterogeneity. Quantifying the interplay in complex composite electrodes with multiscale resolution constitutes a frontier challenge in precisely diagnosing the fading mechanism of batteries. In this study, hard X‐ray phase contrast tomography, capable of nanoprobing thousands of active particles at once, enables an unprecedented statistical analysis of the chemomechanical transformation of composite electrodes under fast charging conditions. The damage heterogeneity is demonstrated to prevail at all length scales, which stems from the unbalanced electron conduction and ionic diffusion, and collectively leads to the nonuniform utilization of active particles spatially and temporally. This study highlights that the statistical mapping of the chemomechanical transformation offers a diagnostic method for the particles utilization and fading, hence could improve electrode formulation for fast‐charging batteries. Abstract : Hard X‐ray phase contrast tomography, capable of nano‐probing thousands of active particles at once, enables an unprecedented statistical analysis of the chemomechanical transformation of composite electrodes under fast charging conditions. This study offers a diagnosing method for the particles utilization and fading, hence could improve the electrode formulation for fast‐charging batteries.